A comparative study of Fagonia arabica fabricated silver sulfide nanoparticles (Ag2S) and silver nanoparticles (AgNPs) with distinct antimicrobial, anticancer, and antioxidant properties - Jatoi, Nouman Rasheed; Khan, Muhammad Aslam; Fida Hussain, Muhammad; Alarjani, Khaloud Mohammed; Elshikh, Mohamed S.; Al Farraj, Dunia; Mansoor, Hafiz Muhammad; Ihsan, Junaid; Bokhari, Syed Ali Imran (Green processing and synthesis, 2024)
Silver sulfide (Ag S) nanomaterials are important chalcogenides and have potential applications in photovoltaic cells, thermoelectric sensors, solar cell batteries, and infrared detectors. However, the biological properties of green synthesized silver sulfide nanoparticles (Ag S-NPs) have been rarely explored as compared to the extensively studied silver nanoparticles (AgNPs). The current study thus investigates and compares synthesized Ag S-NPs and AgNPs for multiple biological properties. Biosynthesis of the NPs is achieved using an aqueous extract of , whereas physicochemical, structural, morphological, and optical characterization of the materials was undertaken using UV–Vis spectroscopy, Fourier transform infrared spectroscopy, X-ray diffractometer, scanning electron microscopy, energy dispersive spectroscopy, photoluminescence, and pH-responsive dispersion studies. Our result reveals that both the NPs exhibit excellent biological properties, yet Ag S-NPs exhibit relatively enhanced antioxidant and anticancer potential against MCF-7 cells. However, AgNPs possess comparatively better antibacterial, antileishmanial, and antifungal properties. Most importantly, both the synthesized NPs are exceptionally well compatible with human blood cells, ensuring their safe and non-toxic properties. Being highly potent and compatible antimicrobial and anticancer materials, the synthesized G-Ag S-NPs and G-AgNPs can be further explored in studies.